Perception of Librarians towards Use of Social Media for Information Service Delivery: A Conceptual Paper - Awurdi, Asabe Pera (American International Journal of Multidisciplinary Scientific Research, 2019)
This study conceptualizes how librarians perceive social media in library and information service delivery. The study consults and review previous research on the use of social media to provide service delivery by librarians by librarians. Social media encourages librarians to create new knowledge, ideas, and services and share it across their community of users. Service delivery is the primary function of any university library. Due to the difficult nature of traditional library services, libraries now embrace and adopt some social media tools for service delivery. This research highlighted the opportunities offer by social media to improve service delivery, the study also discuss the categorization of social media, types of social media, applicability of social media, challenges face by librarians when using social media and strategies on incorporating social media when using service delivery. Based on the conceptual review carried out, majority of studies reveals that librarians use social media and ICT in information service library and the most use form of social media is the Facebook, WhatApps and twitter, but, however, they do encounter obstacles in terms when using the social media. The study concludes that librarians actually use social media for library information service delivery, but yet there is a lot of challenges for proper use of social media in library and information delivery. Therefore, the study recommends that university libraries should incorporate more social media to provide effective services to their clients and adequate finance should be provided regularly by the university management to improve the use of social media in information service delivery and finally librarians should render more proactive and more quality social media services to meet the information needs of clients